Wastewater and Grey Water Footprint Assessment of the Olive Oil Production Process in Northwest Argentina - Vuksinic, Evelyn (2024)
Argentina stands as the leading producer and exporter of olive products in the Americas, with the province of La Rioja as its main productive area. Since the 1990s, the olive grove cultivated area and related agro-industry in La Rioja have expanded. However, the resulting wastewater has generally been neglected. The water footprint (WF) provides information about the water volume consumed and polluted by a production process. Since the 1990s, agricultural and agro-industrial activities in La Rioja have experienced substantial growth. This study aims to analyze the generation, quality, and management of Oil Mill Wastewater (OMWW) using the grey WF of chloride and nitrate as an indicator and focusing on two olive mills (OM) in La Rioja. Additionally, it seeks to examine the relationship between the international trade of provincial olive oil and the estimated grey WF. For the diagnosis of OMWW generation, a description of the production process was made coupled with flow and physico-chemical characterization. The total grey WF was 8.69 and 45.5 L water/L olive oil for OM 1 and OM 2, respectively. Nitrate was identified as the critical pollutant. The grey virtual water export related to the export of olive oil was 5569 m3 for OM 1 and 28,000 m3 for OM 2. Theprovincial grey virtual water export related to olive oil was 161,955 m3 with major trade destinationsincluding Spain, the United States, and Brazil. The article analyses for the first time the grey WF ofolive oil industries and assess the related grey virtual water exports. This research represents a stepforward in the knowledge of wastewater management in the olive oil sector and facilitates the search for solutions to minimize negative environmental impacts while promoting cleaner production.